A bioactive glass-based composite multi-layer cartilage scaffold and preparation method thereof

By adding biochitosan composite microspheres and sodium alginate to the bioactive glass-based composite multi-layer cartilage scaffold, the problem of insufficient mechanical strength of cartilage injury repair in the prior art was solved, and a more effective cartilage repair effect was achieved.

CN119075012BActive Publication Date: 2025-04-04OU SHIBAITAI (BEIJING) BIOTECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411211250.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-04-04
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of repairing cartilage injuries in humans, especially in terms of mechanical strength and individual differences.

Method used

Using a bioactive glass-based composite multi-layer cartilage scaffold, biochitosan composite microspheres are added to the subchondral bone layer and the cartilage transition layer, combined with sodium alginate, to enhance the mechanical strength and cell migration ability of the scaffold.

Benefits of technology

The dual bionic of the cartilage scaffold is realized, which enhances the repair effect, and solves the problem of mechanical strength decline caused by bioactive glass by improving mechanical strength and improving cell migration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020361170000201
    Figure BDA0005020361170000201
  • Figure BDA0005020361170000211
    Figure BDA0005020361170000211
Patent Text Reader

Abstract

The present invention proposes a bioactive glass-based composite multilayer cartilage scaffold and a preparation method thereof, which belongs to the technical field of biological cartilage materials. The cartilage scaffold includes a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top; the subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and a binder, the cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and a binder; the hyaline cartilage layer is composed of hydrogel and a binder. The cartilage scaffold of the present invention can not only promote the generation of growth factors and promote cell reproduction, but also has excellent mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biological cartilage materials, and in particular to a bioactive glass-based composite multi-layer cartilage scaffold and a preparation method thereof. Background Art

[0002] Cartilage is the most difficult structure to heal in the human body. The main function of cartilage is to relieve pressure and act as an elastic cushion to protect the bones under the cartilage from damage. Diseases such as joint trauma and inflammation often cause articular cartilage damage. After articular cartilage damage, the regeneration capacity is limited and it is difficult to repair itself. Even relatively small cartilage damage may produce more obvious symptoms such as pain, swelling, and dysfunction, and eventually joint degeneration. Current clinical methods for treating cartilage damage, such as drug therapy or joint cleaning, can only temporarily relieve pain and cannot cure it; autologous bone transplantation is a traumatic treatment method with good treatment effects, but the source is limited and it cannot repair large defects; allogeneic bone transplantation also has the problem of insufficient sources and is prone to rejection; artificial cartilage is mostly made of metal or ceramic materials, which are prone to loosening and wear after implantation.

[0003] With the rapid development of tissue engineering technology in recent years, people can transplant tissue engineering scaffolds. The ideal tissue engineering scaffold should have good biocompatibility, plasticity, moderate biodegradability and three-dimensional structure, as well as excellent wear resistance, tension resistance and durability. Due to the different pathological mechanisms of cartilage damage in patients, the thickness, texture, structure and biomechanical properties of cartilage in different parts of the body, there are obvious individual differences in human cartilage repair.

[0004] Bioactive glass is a type of biomaterial with excellent performance. It has good bioactivity and biocompatibility. It can effectively accelerate the migration of cells in the wound and upregulate the expression of vascular-related growth factors in the wound. In addition, it can promote the deposition of collagen in the wound, accelerate epithelialization and granulation formation, inhibit bacterial reproduction, and promote wound healing. The degradation products of bioactive glass can promote the production of growth factors and promote cell reproduction. However, bioactive glass is brittle, has low fracture toughness and mechanical strength. Using it as a biocartilage scaffold material will affect the mechanical strength of the biocartilage scaffold. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and propose a bioactive glass-based composite multilayer cartilage scaffold and a preparation method thereof. The cartilage scaffold of the present invention can not only promote the generation of growth factors and promote cell reproduction, but also has excellent mechanical strength.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The present invention provides a bioactive glass-based composite multi-layer cartilage scaffold, comprising a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top; the subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and a binder, the cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and a binder; the hyaline cartilage layer is composed of hydrogel and a binder.

[0008] In the technical solution of the present invention, a cartilage scaffold with a composite multilayer and gradient porous structure is customized and designed in combination with the cartilage defect site and individual characteristics of the patient, which matches the human cartilage structure, realizes the dual bionics of materials and structures, and enhances the repair effect of the cartilage scaffold. In addition, by adding a bioactive glass component to the cartilage scaffold, bioactive glass is a type of biomaterial with excellent performance, which can effectively accelerate the migration of cells at the wound, and upregulate the expression of vascular-related growth factors at the wound (see background technology for details, no more details here), but the brittleness of bioactive glass is large, and the fracture toughness and mechanical strength are low. Using it as a biological cartilage scaffold material will affect the mechanical strength of the biological cartilage scaffold. In order to solve this problem, the present invention improves the mechanical strength of the cartilage scaffold by adding bio-chitosan composite microspheres in the subchondral bone layer and cartilage transition layer containing bioactive glass, and solves the problem of the decrease in the mechanical strength of the cartilage scaffold caused by bioactive glass.

[0009] In the technical solution of the present invention, the prepared bio-chitosan composite microspheres are cored with chitosan microspheres, polyethyleneimine is grafted on the surface of the chitosan microspheres, and the polyethyleneimine molecules have a relatively large number of branched structures. The chitosan composite microspheres are doped into the subchondral bone layer and the cartilage transition layer, which can form a skeleton reinforcement effect on the subchondral bone layer and the cartilage transition layer, greatly improve the mechanical strength of the biological cartilage scaffold, and solve the problem of the mechanical strength of the cartilage scaffold being reduced by the bioactive glass. On the other hand, the chitosan microsphere material prepared by the present invention can also be used as a hydrogel material, and has good compatibility with other hydrogel materials, thereby further improving the mechanical strength of the biological cartilage scaffold.

[0010] As a further improvement of the present invention, the mass ratio of the bioactive glass to the biochitosan composite microspheres in the subchondral bone layer is 1:(0.02-0.08).

[0011] As a further improvement of the present invention, the mass ratio of the bioactive glass, the hydrogel and the biochitosan composite microspheres in the cartilage transition layer is 1:(0.5-1):(0.05-0.1).

[0012] As a further improvement of the present invention, the hydrogel is composed of bacterial cellulose and gelatin;

[0013] The mass ratio of the bacterial cellulose to gelatin is 1:(1-5).

[0014] As a further improvement of the present invention, the binder is selected from one or more of polylactic acid, polyvinyl alcohol, silk fibroin, and collagen.

[0015] As a further improvement of the present invention, the method for preparing the bio-chitosan composite microspheres comprises the following steps:

[0016] 1) adding chitosan into acetic acid solvent, stirring and dissolving to obtain chitosan solution for standby use;

[0017] 2) mixing the liquid paraffin solution and the emulsifier Tween-80 evenly to obtain a mixed oil phase solution, adding the chitosan solution dropwise into the mixed oil phase solution, and then performing ultrasonic vibration to form a water-in-oil emulsion suspension;

[0018] 3) adding glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres;

[0019] 4) adding polyethyleneimine into deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres into the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution;

[0020] 5) adding a 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, subjecting the mixture to an ultrasonic oscillation reaction at 30° C. for 20 h, filtering, separating, washing with water and drying to obtain bio-chitosan composite microspheres.

[0021] As a further improvement of the present invention, sodium alginate is also added to the subchondral bone layer and the cartilage transition layer.

[0022] In the technical solution of the present invention, as mentioned above, the mechanical strength of the cartilage scaffold is improved by adding bio-chitosan composite microspheres to the subchondral bone layer and the cartilage transition layer containing bioactive glass, thereby solving the problem of the decrease in the mechanical strength of the cartilage scaffold caused by bioactive glass. The research and development team found through experimental research that since the prepared biological cartilage scaffold material is a porous structure, after the cartilage scaffold material is freeze-dried, some bio-chitosan composite microspheres are precipitated from the cartilage scaffold, which not only affects the reinforcing effect of the bio-chitosan composite microspheres on the cartilage scaffold, but also causes the clogging of the porous structure of the biological cartilage scaffold, which is not conducive to the penetration of cells into the cartilage scaffold, that is, it is not conducive to the migration and proliferation of cells. In order to further solve the above problems, the research and development team added sodium alginate to the subchondral bone layer and the cartilage transition layer. Sodium alginate is negatively charged, while the polyethyleneimine molecules grafted on the surface of the chitosan microspheres are positively charged. The electrostatic force between the two is used to enhance the binding force between the bio-chitosan composite microspheres and the cartilage scaffold, thereby solving the problem of the precipitation of the bio-chitosan composite microspheres from the cartilage scaffold.

[0023] A method for preparing a bioactive glass-based composite multi-layer cartilage scaffold comprises the following steps:

[0024] a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file;

[0025] b) Preparing slurries: preparing slurry A for printing the subchondral bone layer, slurry B for printing the cartilage transition layer, and slurry C for printing the transparent cartilage layer respectively;

[0026] c) 3D printing: loading the STL format file into a multi-nozzle extrusion bioceramic 3D printing device, installing three dispensing syringes respectively filled with subchondral bone layer printing slurry A, cartilage transition layer printing slurry B and transparent cartilage layer printing slurry C on the printing head for printing; first printing the subchondral bone layer, then printing the cartilage transition layer, and finally printing the transparent cartilage layer; obtaining a cartilage scaffold blank;

[0027] d) Post-processing: The cartilage scaffold blank is freeze-dried and then cleaned, and the cleaned cartilage scaffold blank is sterilized to finally obtain a bioactive glass-based composite multilayer cartilage scaffold.

[0028] The present invention has the following beneficial effects:

[0029] 1) In the technical solution of the present invention, a cartilage scaffold with a composite multi-layer and gradient porous structure is customized and designed in combination with the cartilage defect site and individual characteristics of the patient, which matches the structure of human cartilage, realizes dual bionics of material and structure, and enhances the repair effect of the cartilage scaffold;

[0030] 2) The mechanical strength of the cartilage scaffold was improved by adding bio-chitosan composite microspheres to the subchondral bone layer and cartilage transition layer containing bioactive glass;

[0031] 3) By adding sodium alginate into the subchondral bone layer and the cartilage transition layer, the binding force between the bio-chitosan composite microspheres and the cartilage scaffold is enhanced, thereby preventing the bio-chitosan composite microspheres from precipitating out of the bio-cartilage scaffold. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The bioactive glass used in the embodiments of the present invention is a biomedical active material, with SiO 2 、Na 2 O, CaO, P 2 O 5 It is the main ingredient and the manufacturer is Zhangjiagang Lanzhi Biotechnology Co., Ltd.

[0033] Example 1

[0034] A bioactive glass-based composite multi-layer cartilage scaffold, comprising a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top;

[0035] The subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and polyvinyl alcohol binder, the mass ratio of the bioactive glass to the biochitosan composite microspheres is 1:0.07, and the added amount of the polyvinyl alcohol binder is 20wt% of the bioactive glass.

[0036] The cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:4, the mass ratio of the bioactive glass, hydrogel and biochitosan composite microspheres is 1:0.9:0.08, and the added amount of the polyvinyl alcohol binder is 30wt% of the bioactive glass.

[0037] The hyaline cartilage layer is composed of hydrogel and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:4, and the added amount of the polyvinyl alcohol binder is 15wt% of the hydrogel.

[0038] The polyvinyl alcohol binder is a polyvinyl alcohol aqueous solution with a mass concentration of 10%.

[0039] Preparation of bio-chitosan composite microspheres:

[0040] 1) Add 0.5 g of chitosan into 50 mL of acetic acid solvent, stir and dissolve to obtain a chitosan solution for later use;

[0041] 2) 500 mL of liquid paraffin solution and 0.05 g of emulsifier Tween-80 were mixed evenly to obtain a mixed oil phase solution, the chitosan solution was added dropwise to the mixed oil phase solution, and then ultrasonically vibrated to form a water-in-oil emulsion suspension;

[0042] 3) adding 0.1 g of glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres;

[0043] 4) adding 1 g of polyethyleneimine to 200 mL of deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres to the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution;

[0044] 5) Add 2 mL of 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, perform ultrasonic oscillation reaction at 30° C. for 20 h, and obtain bio-chitosan composite microspheres through filtration, separation, water washing and drying.

[0045] A method for preparing a bioactive glass-based composite multi-layer cartilage scaffold comprises the following steps:

[0046] a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file;

[0047] b) Preparation of slurry:

[0048] The bioactive glass, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a subchondral bone layer printing slurry A;

[0049] The bioactive glass, hydrogel, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed to obtain a cartilage transition layer printing slurry B;

[0050] The hydrogel and the polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a transparent cartilage layer printing slurry C;

[0051] The mass ratio of the printing paste A, printing paste B and printing paste C is 1:0.5:1.

[0052] C) Load the STL format file established for the cartilage defect model in a) above into a multi-nozzle extrusion bioceramic 3D printing device, and then place three dispensing syringes filled with different printing slurries on the print head, and use the above-treated printing slurry for 3D printing. During the printing process, first print the subchondral bone layer structure, using slurry A for printing, with a porosity of 40% gradient structure, then print the cartilage transition layer, using slurry B for printing, with a porosity of 60% gradient structure, and finally print the transparent cartilage layer, using slurry C for printing, with a porosity of 80% gradient structure, to obtain a composite multilayer cartilage scaffold;

[0053] d) Post-processing: The printed composite multi-layer cartilage scaffold is placed in a freeze dryer for freeze drying. After freeze drying, the cartilage scaffold is placed in sterile injection water for ultrasonic cleaning for 1 hour, and then placed in a freeze dryer for freeze drying. This is repeated once. Finally, the composite multi-layer cartilage scaffold is sterilized by low-temperature sterilization and packaged after sterilization.

[0054] Example 2

[0055] A bioactive glass-based composite multi-layer cartilage scaffold, comprising a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top;

[0056] The subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and polyvinyl alcohol binder, the mass ratio of the bioactive glass to the biochitosan composite microspheres is 1:0.03, and the added amount of the polyvinyl alcohol binder is 20wt% of the bioactive glass.

[0057] The cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:2, the mass ratio of the bioactive glass, hydrogel and biochitosan composite microspheres is 1:0.6:0.06, and the added amount of the polyvinyl alcohol binder is 30wt% of the bioactive glass.

[0058] The hyaline cartilage layer is composed of hydrogel and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:2, and the added amount of the polyvinyl alcohol binder is 15wt% of the hydrogel.

[0059] The polyvinyl alcohol binder is a polyvinyl alcohol aqueous solution with a mass concentration of 10%.

[0060] Preparation of bio-chitosan composite microspheres:

[0061] 1) Add 0.5 g of chitosan into 50 mL of acetic acid solvent, stir and dissolve to obtain a chitosan solution for later use;

[0062] 2) 500 mL of liquid paraffin solution and 0.05 g of emulsifier Tween-80 were mixed evenly to obtain a mixed oil phase solution, the chitosan solution was added dropwise to the mixed oil phase solution, and then ultrasonically vibrated to form a water-in-oil emulsion suspension;

[0063] 3) adding 0.1 g of glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres;

[0064] 4) adding 1 g of polyethyleneimine to 200 mL of deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres to the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution;

[0065] 5) Add 2 mL of 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, perform ultrasonic oscillation reaction at 30° C. for 20 h, and obtain bio-chitosan composite microspheres through filtration, separation, water washing and drying.

[0066] A method for preparing a bioactive glass-based composite multi-layer cartilage scaffold comprises the following steps:

[0067] a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file;

[0068] b) Preparation of slurry:

[0069] The bioactive glass, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a subchondral bone layer printing slurry A;

[0070] The bioactive glass, hydrogel, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed to obtain a cartilage transition layer printing slurry B;

[0071] The hydrogel and the polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a transparent cartilage layer printing slurry C;

[0072] The mass ratio of the printing paste A, printing paste B and printing paste C is 1:0.5:1.

[0073] C) Load the STL format file established for the cartilage defect model in a) above into a multi-nozzle extrusion bioceramic 3D printing device, and then place three dispensing syringes filled with different printing slurries on the print head, and use the above-treated printing slurry for 3D printing. During the printing process, first print the subchondral bone layer structure, using slurry A for printing, with a porosity of 40% gradient structure, then print the cartilage transition layer, using slurry B for printing, with a porosity of 60% gradient structure, and finally print the transparent cartilage layer, using slurry C for printing, with a porosity of 80% gradient structure, to obtain a composite multilayer cartilage scaffold;

[0074] d) Post-processing: The printed composite multi-layer cartilage scaffold is placed in a freeze dryer for freeze drying. After freeze drying, the cartilage scaffold is placed in sterile injection water for ultrasonic cleaning for 1 hour, and then placed in a freeze dryer for freeze drying. This is repeated once. Finally, the composite multi-layer cartilage scaffold is sterilized by low-temperature sterilization and packaged after sterilization.

[0075] Example 3

[0076] A bioactive glass-based composite multi-layer cartilage scaffold, comprising a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top;

[0077] The subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and polyvinyl alcohol binder, the mass ratio of the bioactive glass to the biochitosan composite microspheres is 1:0.05, and the added amount of the polyvinyl alcohol binder is 20wt% of the bioactive glass.

[0078] The cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:3, the mass ratio of the bioactive glass, hydrogel and biochitosan composite microspheres is 1:0.8:0.07, and the added amount of the polyvinyl alcohol binder is 30wt% of the bioactive glass.

[0079] The hyaline cartilage layer is composed of hydrogel and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:3, and the added amount of the polyvinyl alcohol binder is 15wt% of the hydrogel.

[0080] The polyvinyl alcohol binder is a polyvinyl alcohol aqueous solution with a mass concentration of 10%.

[0081] Preparation of bio-chitosan composite microspheres:

[0082] 1) Add 0.5 g of chitosan into 50 mL of acetic acid solvent, stir and dissolve to obtain a chitosan solution for later use;

[0083] 2) 500 mL of liquid paraffin solution and 0.05 g of emulsifier Tween-80 were mixed evenly to obtain a mixed oil phase solution, the chitosan solution was added dropwise to the mixed oil phase solution, and then ultrasonically vibrated to form a water-in-oil emulsion suspension;

[0084] 3) adding 0.1 g of glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres;

[0085] 4) adding 1 g of polyethyleneimine to 200 mL of deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres to the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution;

[0086] 5) Add 2 mL of 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, perform ultrasonic oscillation reaction at 30° C. for 20 h, and obtain bio-chitosan composite microspheres through filtration, separation, water washing and drying.

[0087] A method for preparing a bioactive glass-based composite multi-layer cartilage scaffold comprises the following steps:

[0088] a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file;

[0089] b) Preparation of slurry:

[0090] The bioactive glass, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a subchondral bone layer printing slurry A;

[0091] The bioactive glass, hydrogel, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed to obtain a cartilage transition layer printing slurry B;

[0092] The hydrogel and the polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a transparent cartilage layer printing slurry C;

[0093] The mass ratio of the printing paste A, printing paste B and printing paste C is 1:0.5:1.

[0094] C) Load the STL format file established for the cartilage defect model in a) above into a multi-nozzle extrusion bioceramic 3D printing device, and then place three dispensing syringes filled with different printing slurries on the print head, and use the above-treated printing slurry for 3D printing. During the printing process, first print the subchondral bone layer structure, using slurry A for printing, with a porosity of 40% gradient structure, then print the cartilage transition layer, using slurry B for printing, with a porosity of 60% gradient structure, and finally print the transparent cartilage layer, using slurry C for printing, with a porosity of 80% gradient structure, to obtain a composite multilayer cartilage scaffold;

[0095] d) Post-processing: The printed composite multi-layer cartilage scaffold is placed in a freeze dryer for freeze drying. After freeze drying, the cartilage scaffold is placed in sterile injection water for ultrasonic cleaning for 1 hour, and then placed in a freeze dryer for freeze drying. This is repeated once. Finally, the composite multi-layer cartilage scaffold is sterilized by low-temperature sterilization and packaged after sterilization.

[0096] Example 4

[0097] A bioactive glass-based composite multi-layer cartilage scaffold, comprising a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top;

[0098] The subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and polyvinyl alcohol binder, the mass ratio of the bioactive glass to the biochitosan composite microspheres is 1:0.08, and the added amount of the polyvinyl alcohol binder is 20wt% of the bioactive glass.

[0099] The cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:5, the mass ratio of the bioactive glass, hydrogel and biochitosan composite microspheres is 1:1:0.1, and the added amount of the polyvinyl alcohol binder is 30wt% of the bioactive glass.

[0100] The hyaline cartilage layer is composed of hydrogel and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:5, and the added amount of polyvinyl alcohol binder is 15wt% of the hydrogel.

[0101] The polyvinyl alcohol binder is a polyvinyl alcohol aqueous solution with a mass concentration of 10%.

[0102] Preparation of bio-chitosan composite microspheres:

[0103] 1) Add 0.5 g of chitosan into 50 mL of acetic acid solvent, stir and dissolve to obtain a chitosan solution for later use;

[0104] 2) 500 mL of liquid paraffin solution and 0.05 g of emulsifier Tween-80 were mixed evenly to obtain a mixed oil phase solution, the chitosan solution was added dropwise to the mixed oil phase solution, and then ultrasonically vibrated to form a water-in-oil emulsion suspension;

[0105] 3) adding 0.1 g of glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres;

[0106] 4) adding 1 g of polyethyleneimine to 200 mL of deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres to the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution;

[0107] 5) Add 2 mL of 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, perform ultrasonic oscillation reaction at 30° C. for 20 h, and obtain bio-chitosan composite microspheres through filtration, separation, water washing and drying.

[0108] A method for preparing a bioactive glass-based composite multi-layer cartilage scaffold comprises the following steps:

[0109] a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file;

[0110] b) Preparation of slurry:

[0111] The bioactive glass, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a subchondral bone layer printing slurry A;

[0112] The bioactive glass, hydrogel, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed to obtain a cartilage transition layer printing slurry B;

[0113] The hydrogel and the polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a transparent cartilage layer printing slurry C;

[0114] The mass ratio of the printing paste A, printing paste B and printing paste C is 1:0.5:1.

[0115] C) Load the STL format file established for the cartilage defect model in a) above into a multi-nozzle extrusion bioceramic 3D printing device, and then place three dispensing syringes filled with different printing slurries on the print head, and use the above-treated printing slurry for 3D printing. During the printing process, first print the subchondral bone layer structure, using slurry A for printing, with a porosity of 40% gradient structure, then print the cartilage transition layer, using slurry B for printing, with a porosity of 60% gradient structure, and finally print the transparent cartilage layer, using slurry C for printing, with a porosity of 80% gradient structure, to obtain a composite multilayer cartilage scaffold;

[0116] d) Post-processing: The printed composite multi-layer cartilage scaffold is placed in a freeze dryer for freeze drying. After freeze drying, the cartilage scaffold is placed in sterile injection water for ultrasonic cleaning for 1 hour, and then placed in a freeze dryer for freeze drying. This is repeated once. Finally, the composite multi-layer cartilage scaffold is sterilized by low-temperature sterilization and packaged after sterilization.

[0117] Example 5

[0118] A bioactive glass-based composite multi-layer cartilage scaffold, comprising a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top;

[0119] The subchondral bone layer is composed of bioactive glass, biochitosan composite microspheres and polyvinyl alcohol binder, the mass ratio of the bioactive glass to the biochitosan composite microspheres is 1:0.02, and the added amount of the polyvinyl alcohol binder is 20wt% of the bioactive glass.

[0120] The cartilage transition layer is composed of bioactive glass, hydrogel, biochitosan composite microspheres and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:1, the mass ratio of the bioactive glass, hydrogel and biochitosan composite microspheres is 1:0.5:0.05, and the added amount of the polyvinyl alcohol binder is 30wt% of the bioactive glass.

[0121] The hyaline cartilage layer is composed of hydrogel and polyvinyl alcohol binder; the hydrogel is composed of bacterial cellulose and gelatin, the mass ratio of bacterial cellulose to gelatin is 1:1, and the added amount of the polyvinyl alcohol binder is 15wt% of the hydrogel.

[0122] The polyvinyl alcohol binder is a polyvinyl alcohol aqueous solution with a mass concentration of 10%.

[0123] Preparation of bio-chitosan composite microspheres:

[0124] 1) Add 0.5 g of chitosan into 50 mL of acetic acid solvent, stir and dissolve to obtain a chitosan solution for later use;

[0125] 2) 500 mL of liquid paraffin solution and 0.05 g of emulsifier Tween-80 were mixed evenly to obtain a mixed oil phase solution, the chitosan solution was added dropwise to the mixed oil phase solution, and then ultrasonically vibrated to form a water-in-oil emulsion suspension;

[0126] 3) adding 0.1 g of glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres;

[0127] 4) adding 1 g of polyethyleneimine to 200 mL of deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres to the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution;

[0128] 5) Add 2 mL of 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, perform ultrasonic oscillation reaction at 30° C. for 20 h, and obtain bio-chitosan composite microspheres through filtration, separation, water washing and drying.

[0129] A method for preparing a bioactive glass-based composite multi-layer cartilage scaffold comprises the following steps:

[0130] a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file;

[0131] b) Preparation of slurry:

[0132] The bioactive glass, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a subchondral bone layer printing slurry A;

[0133] The bioactive glass, hydrogel, bio-chitosan composite microspheres and polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed to obtain a cartilage transition layer printing slurry B;

[0134] The hydrogel and the polyvinyl alcohol binder are mixed according to a ratio, and after mixing, they are placed in a slurry homogenizer for stirring to make them evenly mixed, and then loaded into a dispensing syringe, and degassed in a centrifuge to make them evenly mixed, thereby obtaining a transparent cartilage layer printing slurry C;

[0135] The mass ratio of the printing paste A, printing paste B and printing paste C is 1:0.5:1.

[0136] C) Load the STL format file established for the cartilage defect model in a) above into a multi-nozzle extrusion bioceramic 3D printing device, and then place three dispensing syringes filled with different printing slurries on the print head, and use the above-treated printing slurry for 3D printing. During the printing process, first print the subchondral bone layer structure, using slurry A for printing, with a porosity of 40% gradient structure, then print the cartilage transition layer, using slurry B for printing, with a porosity of 60% gradient structure, and finally print the transparent cartilage layer, using slurry C for printing, with a porosity of 80% gradient structure, to obtain a composite multilayer cartilage scaffold;

[0137] d) Post-processing: The printed composite multi-layer cartilage scaffold is placed in a freeze dryer for freeze drying. After freeze drying, the cartilage scaffold is placed in sterile injection water for ultrasonic cleaning for 1 hour, and then placed in a freeze dryer for freeze drying. This is repeated once. Finally, the composite multi-layer cartilage scaffold is sterilized by low-temperature sterilization and packaged after sterilization.

[0138] Example 6

[0139] The difference between Example 6 and Example 5 is that:

[0140] Sodium alginate is also added to the subchondral bone layer and the cartilage transition layer;

[0141] The amount of sodium alginate added to the subchondral bone layer is 5wt% of the bioactive glass;

[0142] The amount of sodium alginate added to the cartilage transition layer is 10wt% of the bioactive glass;

[0143] The remaining steps are the same as those in Example 5.

[0144] Comparative Example 1

[0145] The difference between Comparative Example 1 and Example 1 is:

[0146] No bio-chitosan composite microspheres are added to the subchondral bone layer and the cartilage transition layer;

[0147] The remaining steps are the same as those in Example 1.

[0148] Comparative Example 2

[0149] The difference between Comparative Example 1 and Example 1 is:

[0150] Add bio-chitosan composite microspheres to the subchondral bone layer and cartilage transition layer

[0151] Replaced with ordinary chitosan microspheres,

[0152] The remaining steps are the same as those in Example 1.

[0153] Performance Testing

[0154] 1. Mechanical properties test:

[0155] Tensile performance test: A universal tensile machine (SHIMADZUAGS-X100N) was used to test the mechanical properties of the cartilage scaffolds, with a tensile speed of 50 mm / min and a strain rate of 0.2% / s. The cartilage scaffolds (20 mm long, 10 mm wide, and 2 mm high) for the tensile test were stretched in a uniaxial manner until they broke. All cartilage scaffold samples were soaked in deionized water to maintain sufficient swelling before testing. Three parallel samples were tested in each group. Compression performance test: The biological cartilage scaffold samples (15 mm high and 10 mm in diameter) were tested for compressive strength using a universal testing machine and compressed to 1 / 2 of their original height for 10 cycles, with three parallel samples tested in each group. The test results are shown in Table 1.

[0156] Table 1

[0157]

[0158] 2. Porosity test:

[0159] The porosity of the sample was determined by liquid replacement method, and the medium used was ethanol. The specific operation was as follows: Weigh the freeze-dried sample, denoted as M 1 In order to make the sample fully absorb anhydrous ethanol, the sample was completely immersed in anhydrous ethanol and placed in a shaker for 24 hours (25°C, 80 rpm). The sample that had been saturated with adsorption was taken out, and the excess liquid on the surface was absorbed with filter paper and then weighed quickly, which was recorded as M. 2 , and then place the sample in a measuring cylinder containing a fixed volume of anhydrous ethanol, and record the volume increment in the measuring cylinder as V. The porosity P of the sample is calculated by the following formula, and the test structure is shown in Table 2.

[0160] P(%)=(M 1 -M 2 ) / ρV; where ρ is the density of anhydrous ethanol (0.8 g / cm 3 ).

[0161] Table 2

[0162] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Porosity (%) 80.6 81.1 80.7 81.5 80.3 85.6

[0163] 3. Degradation performance test:

[0164] The in vitro degradation rate of the cartilage scaffold was detected by weight loss, and the initial weight of the cartilage scaffold (W 0 ), soak the sample in 2 mL of PBS solution containing lysozyme (15 mg / mL, pH = 7.4), and shake it at 37°C, 140 r / min in a constant temperature shaker for 40 days to accelerate its degradation. After taking it out, wipe off the excess water on the surface of the sample and weigh it, recording it as W tThe degradation rate (J) was calculated by the following formula. All samples were tested in triplicate. The test results are shown in Table 3.

[0165] J=(W 0 -W t ) / W 0 *100%;

[0166] Table 3

[0167]

[0168] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A bioactive glass-based composite multi-layer cartilage scaffold, characterized in that: It comprises a subchondral bone layer, a cartilage transition layer and a hyaline cartilage layer stacked in sequence from bottom to top; the subchondral bone layer is composed of bioactive glass, bio-chitosan composite microspheres, sodium alginate and a binder, the cartilage transition layer is composed of bioactive glass, hydrogel, bio-chitosan composite microspheres, sodium alginate and a binder; the hyaline cartilage layer is composed of hydrogel and a binder; The preparation method of the bio-chitosan composite microspheres comprises the following steps: 1) adding chitosan into acetic acid solvent, stirring and dissolving to obtain chitosan solution for standby use; 2) mixing the liquid paraffin solution and the emulsifier Tween-80 evenly to obtain a mixed oil phase solution, adding the chitosan solution dropwise into the mixed oil phase solution, and then performing ultrasonic vibration to form a water-in-oil emulsion suspension; 3) adding glutaraldehyde crosslinking agent to the water-in-oil emulsion suspension, heating to 60° C., performing ultrasonic oscillation reaction, filtering, separating, washing and vacuum drying to obtain chitosan microspheres; 4) adding polyethyleneimine into deionized water and stirring to dissolve to obtain a polyethyleneimine solution, adding chitosan microspheres into the polyethyleneimine solution, and ultrasonically oscillating to uniformly disperse the chitosan microspheres in the polyethyleneimine solution to obtain a chitosan microsphere-polyethyleneimine mixed solution; 5) adding a 0.5 mol / L sodium hydroxide solution to the chitosan microsphere-polyethyleneimine mixture, subjecting the mixture to an ultrasonic oscillation reaction at 30° C. for 20 h, filtering, separating, washing with water and drying to obtain bio-chitosan composite microspheres.

2. The bioactive glass-based composite multi-layer cartilage scaffold according to claim 1, characterized in that: The mass ratio of the bioactive glass to the biochitosan composite microspheres in the subchondral bone layer is 1:(0.02-0.08).

3. The bioactive glass-based composite multi-layer cartilage scaffold according to claim 1, characterized in that: The mass ratio of the bioactive glass, the hydrogel and the bio-chitosan composite microspheres in the cartilage transition layer is 1:(0.5-1):(0.05-0.1).

4. The bioactive glass-based composite multi-layer cartilage scaffold according to claim 1, characterized in that: The hydrogel consists of bacterial cellulose and gelatin; The mass ratio of the bacterial cellulose to gelatin is 1:(1-5).

5. The bioactive glass-based composite multi-layer cartilage scaffold according to claim 1, characterized in that: The binder is selected from one or more of polylactic acid, polyvinyl alcohol, silk fibroin, and collagen.

6. A method for preparing the bioactive glass-based composite multi-layer cartilage scaffold according to any one of claims 1 to 5, characterized in that: The following steps are involved: a) Obtaining a cartilage defect model: obtaining the tomographic data of the cartilage defect site of the patient through medical imaging, performing three-dimensional reconstruction through the tomographic data, and designing a model, wherein pores are set in the model and saved as an STL format file; b) Preparing slurries: preparing slurry A for printing the subchondral bone layer, slurry B for printing the cartilage transition layer, and slurry C for printing the transparent cartilage layer respectively; c) 3D printing: loading the STL format file into a multi-nozzle extrusion bioceramic 3D printing device, installing three dispensing syringes respectively filled with subchondral bone layer printing slurry A, cartilage transition layer printing slurry B and transparent cartilage layer printing slurry C on the printing head for printing; first printing the subchondral bone layer, then printing the cartilage transition layer, and finally printing the transparent cartilage layer; obtaining a cartilage scaffold blank; d) Post-processing: The cartilage scaffold blank is freeze-dried and then cleaned, and the cleaned cartilage scaffold blank is sterilized to finally obtain a bioactive glass-based composite multilayer cartilage scaffold.

Citation Information

Patent Citations

  • Preparation method of drug bearing microsphere / chitosan / sodium alginate injectable aquogel

    CN103446624A

  • Osteochondral integrated repairing gradient hybrid support material and preparation method thereof

    CN108525012A

  • Biological scaffold as well as preparation method and application thereof

    CN115212353A